COVID-19 Pandemic in Indonesia: Some Reflections from Bażl Al-Māʿūn by Ibn Ḥajr al-ʿAsqalānī - Qudsy, Saifuddin Zuhri; Pabbajah, Mustaqim; Jubba, Hasse; Zain, Muhammad; Syafera, Arkan (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
History and pandemics are two inseparable entities, yet often forgotten. The occurrence of a pandemic in a certain time and place has always become a critical object of study and documentation, thus generating innumerable research literature. This research attempts to re-state the urgency of historical literature as a source of knowledge on dealing with the Covid-19 crisis through the religious scholars’ approach. The data were compiled through observation and literature review with content analysis method on Bażl al-Māʿūn of Ibn Ḥajr al-ʿAsqalānī, a classic book containing pandemic studies sourced from hadith and the history of the early Muslim community. The result of this study reveals that classical religious literature as historical knowledge could provide contextual solutions for society. The study of the historical works not only gives clues on the past events but also provides material to contextualise the attempt to build newly-induced awareness in the community. Learning from past events teaches society that pandemics are recurring events. Some similarities and differences are seen in every part of the pandemic. Thus, religious scholars serve as agents who disseminate the lesson learned from the past to prevent the recurrence of similar events in the future. This way, people of today should refer to the past to set some appropriate strategies for coping with the pandemic. Likewise, a historical account mentions the relevance of some terminologies that are currently used around Covid-19.